Pelaksanaan Pendidikan Budi Pekerti Di SD Negeri 8 Sumerta Kecamatan Denpasar Timur - Ayu Ratih Nakayanti (Jayapangus Press, 2018)
Character education includes morality or immorality that is very useful for a child when the child has grown up. Character education aims to build the character of a child, to be a good child who radiates noble traits. The scope of education is related to the teachings of morality implanted, grown in a child, since in the womb, in the family, in school and in the community, the main source or material of character education is religious teachings. Shifting values, attitudes and behavior as difficult to be dammed due to the rapid flow of information without borders which is one of the negative factors of technological development, especially the development of adolescent life in general and learners in particular. From some of these things arise due to the shift in values, attitudes and behavior is very necessary to be anticipated as early as possible through the education of character. To build and improve again so that learners behave, behave, ethics and morals in accordance with the values ​​and norms of religious teachings, the steps that must be done is to develop mental, character, character and personality of the bad to be good for the realization of learners who are intelligent and have the attitude and behavior in accordance with the values ​​and norms of religious teachings.